Population-Based Resequencing of LIPG and ZNF202 Genes in Subjects with Extreme HDL Levels - Razzaghi, Hamid; Santorico, Stephanie A.; Kamboh, M I. (Frontiers in Genetics, 2012)
Endothelial lipase (LIPG) and zinc finger protein 202 (ZNF202) are two pivotal genes in HDL metabolism, and therefore, it is important to understand the impact their sequence variants may have on HDL cholesterol levels. We resequenced the entire both genes in White and Hispanic individuals having high ( =75.90 mg/dl, n=114) or low ( =31.24 mg/dl, n=121) HDL cholesterol levels, and identified a total of 185 and 122 sequence variants in LIPG and ZNF202, respectively. We found only two missense variants in LIPG (T111I and N396S) and two in ZNF202 (A154V and K259E). In both genes, there were several rare variants unique to either the low or high HDL group. For LIPG, the proportion of unique variants differed between the high and low HDL groups in both Whites (p=0.022) and Hispanics (p=0.017), but for ZNF202 this difference was observed only in Hispanics (p=0.021). We also identified a common haplotype in ZNF202 among Whites that was significantly associated with high HDL group (p=0.0133). These findings provide insights into the genetics of LIPG and ZNF202, and suggest that sequence variants occurring with high frequency in non-exonic regions may play a prominent role in modulating HDL-C levels in the general population.